Wykonaj mnożenie sum algebraicznych

Wykonaj Mnożenie Sum Algebraicznych class=

Odpowiedź :

Odpowiedź:

[tex]a)\ \ (y-4)(y+3)=y\cdot y+3y-4y-4\cdot3=y^2-y-12\\\\b)\ \ (t-1)(5t-2)=t\cdot5t-2t-5t-1\cdot(-2)=5t^2-7t+2\\\\c)\ \ (k^2-4)(2k+1)=k^2\cdot2k+k^2\cdot1-4\cdot2k-4\cdot1=2k^3+k^2-8k-4\\\\d)\ \ (3a-5)(2a-1)=3a\cdot2a-3a\cdot1-5\cdot2a-5\cdot(-1)=6a^2-3a-10a+5=\\\\=6a^2-13a+5[/tex]

[tex]e)\ \ (c-2)(c^2+c+1)=c\cdot c^2+c\cdot c+c-2c^2-2c-2\cdot1=c^3+c^2+c-2c^2-2c-2=\\\\=c^3-c^2-c-2\\\\f)\ \ (x+4)(x^2-x-2)=x\cdot x^2-x\cdot x-2x+4x^2-4x+4\cdot(-2)=\\\\=x^3-x^2-2x+4x^2-4x-8=x^3+3x^2-6x-8\\\\g)\ \ (u-1)(u^2-3u+7)=u\cdot u^2-u\cdot3u+7u-u^2-1\cdot(-3u)-1\cdot7=\\\\=u^3-3u^2+7u-u^2+3u-7=u^3-4u^2+10u-7[/tex]